Prognostic Factors for Recovery in Bell’s Palsy - Marques Gomes, Pedro; Cunha Cabral, Diogo; Alves Carção, André; Ferreira Penêda, José; Duarte, Delfim; Azevedo, Paula (ENT Updates, 2024)
Background: To evaluate prognostic factors and the effects of pharmacologic and non-pharmacologic therapeutic interventions on the recovery of patients with Bell´s Palsy (BP). Methods: Cross-sectional study of patients admitted to a tertiary hospital with a diagnosis of BP between January 2010 and December 2020. Variables assessed: affected hemiface, degree of BP, comorbidities, smoking history, pharmacological treatment, physiotherapy and degree of recovery at third month. Results: A total of 87 patients were enrolled. No statistically signifcant difference was found between patients treated with corticosteroids and those treated with corticosteroids in combination with antivirals. Similarly, no statistically signifcant difference was observed between patients who received physiotherapy and those who did not. Hypertension, smoking, and higher grade H-B were associated with incomplete recovery (P=.042, .014, .028, and .037, respectively) and were identifed as predictors of poor prognosis. A hypertensive patient is 3.020 times more likely to have an incomplete recovery than a normotensive patient (P=.047, CI: 1.017-8.967), while a smoker is 3.897 times more likely to have an incomplete recovery than a non-smoker (P=.018, CI: 1.263-12.208). Patients with H-B grade V are 10.714 times more likely to have an incomplete recovery than patients with H-B grade II (P=.046, CI: 1.046-109.784). Conclusion: Hypertension, smoking, and higher H-B grade were signifcantly associated with incomplete recovery and poor prognosis. Patients treated with corticosteroids alone or in combination with antivirals showed no signifcant difference in the recovery rate. Similarly, no statistically signifcant difference was observed between patients who received physiotherapy and those who did not.